2008
DOI: 10.1111/j.1365-2753.2007.00832.x
|View full text |Cite
|
Sign up to set email alerts
|

Natural history and effectiveness of early detection of Parkinson’s disease: results from two community‐based programmes in Taiwan (KCIS no. 11)

Abstract: The present study recommended a 5-yearly screening programme, with 74% of PD cases prevented from progressing to H-Y stage III or worse within 10 years of diagnosis, and leading to a corresponding 26% reduction in mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Patients in H&Y 1 to 3 were assumed to have an excess mortality rate equal to the newly diagnosed cohort; the H&Y 4 rate was assumed to equal the AAD cohort; and the H&Y 5 rate was assumed to equal the institutionalized cohort. Previous studies have also demonstrated an association between PD progression and mortality …”
Section: Methodsmentioning
confidence: 79%
“…Patients in H&Y 1 to 3 were assumed to have an excess mortality rate equal to the newly diagnosed cohort; the H&Y 4 rate was assumed to equal the AAD cohort; and the H&Y 5 rate was assumed to equal the institutionalized cohort. Previous studies have also demonstrated an association between PD progression and mortality …”
Section: Methodsmentioning
confidence: 79%
“…This survey was part of a population screening service, the Keelung Community-Based Integrated Screening (KCIS) program. The implementation and preliminary findings of the KCIS program have been described in detail elsewhere [19][20][21][22][23] . Briefly, the KCIS program is a multiple disease screening service targeted at residents over 30 years old living in Keelung.…”
Section: Keelung Population-based Screenmentioning
confidence: 99%
“…In order to cover at least one round of screening for each resident from 1999 to 2005, every year we invited participants based on the residence registry to attend the KCIS program at screening centers covering 7 districts of Keelung City. To investigate the prevalence rate of IPD, the IPD survey was integrated into this screening service from January 1, 2001 to December 31, 2001 [20] . All screening activities were implemented in an administrative unit, called 'Lii'.…”
Section: Keelung Population-based Screenmentioning
confidence: 99%
“…To the Editor : Previous studies of the early detection of idiopathic Parkinson's disease (IPD) raised the possibility of introducing population‐based screening to detect IPD in the early stage . It is therefore of great interest to assess the IPD detection rates of different methods.…”
mentioning
confidence: 99%